2014
DOI: 10.1017/s0007123414000374
|View full text |Cite
|
Sign up to set email alerts
|

Conflict will Harden your Heart: Exposure to Violence, Psychological Distress, and Peace Barriers in Israel and Palestine

Abstract: Does exposure to political violence prompt civilians to support peace? We investigate the determinants of civilian attitudes toward peace during ongoing conflict using two original panel datasets representing Israelis (n=996) and Palestinians in East Jerusalem, the West Bank and Gaza (n=631) (149 communities in total). A multi-group estimation analysis shows that individual-level exposure to terrorism and political violence makes the subject populations less likely to support peace efforts. The findings also c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
100
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 131 publications
(107 citation statements)
references
References 61 publications
7
100
0
Order By: Relevance
“…Prolonged exposure to political violence can act as a stressor that leads to anger, anxiety, and depression (Garbarino and Kostelny 1996). Studies examining the effect of the Israeli-Palestinian conflict on support for extremism find that both direct and indirect exposure to conflict increase negative emotions and feelings that an individual or group is under threat from the other or out-group (Heath et al 2013;Hirsch-Hoefler et al 2014;Hobfoll et al 2009;Huesmann et al 2017). Hirsch-Hoefler et al (2014) found that Israelis and Palestinians exposed to political violence were more likely to report psychological distress, perceive group threat, and less likely to support peaceful means of political conflict resolution.…”
Section: Theoretical Background General Strain Theorymentioning
confidence: 99%
“…Prolonged exposure to political violence can act as a stressor that leads to anger, anxiety, and depression (Garbarino and Kostelny 1996). Studies examining the effect of the Israeli-Palestinian conflict on support for extremism find that both direct and indirect exposure to conflict increase negative emotions and feelings that an individual or group is under threat from the other or out-group (Heath et al 2013;Hirsch-Hoefler et al 2014;Hobfoll et al 2009;Huesmann et al 2017). Hirsch-Hoefler et al (2014) found that Israelis and Palestinians exposed to political violence were more likely to report psychological distress, perceive group threat, and less likely to support peaceful means of political conflict resolution.…”
Section: Theoretical Background General Strain Theorymentioning
confidence: 99%
“…The dead are few; it is the living whose daily lives are transformed by the constant fear of impending doom. Conventional terrorism exacerbates feelings of insecurity and perceptions of threat that prompt public cries for protective and militant government policies that can short-circuit public discourse, intensify intolerance for dissident views, and infringe on human rights (Boggs 2002; Hirsch-Hoefler et al, 2014). Does cyber terrorism cause similar effects?…”
Section: Defining Cyber Terrorismmentioning
confidence: 99%
“…Dyrstad (2012Dyrstad ( , 2013, for example, has measured "direct individual exposure", but operationalised it as whether the respondent had a close friend or family member die or disappear, which is in fact an indirect war experience. Massey et al (2003) have calculated a war experience index based on both personal experiences (such as whether one's life was endangered or whether one was wounded) and events that happened to friends and family members (see also Canetti et al 2017;Canetti-Nisim et al 2009;Hirsch-Hoefler et al 2016). Moreover, they included a separate measure for having been in personal danger during the war, which created a conceptual overlap between their independent variables.…”
Section: Voters' War Experiences: Combatants Civilians and War Traumamentioning
confidence: 99%
“…This ethos of conflict subsequently shapes political attitudes. The model has proven effective in explaining exclusionist attitudes in Israel toward Palestinians (Canetti-Nisim et al 2009), and attitudes toward what a peace settlement with the Palestinians should look like (Canetti-Nisim et al 2009;Hirsch-Hoefler et al 2016; also see Solomon and Lavi 2005).…”
Section: Voters' War Experiences: Combatants Civilians and War Traumamentioning
confidence: 99%